Teologi Oratorium sebagai Liturgi Ibadah Kreatif-Konstruktif di Jemaat Gmibm Pniel Tumobui - Kalalo, Jefry; Baranoi, Crestio Yesaya; Ingkiriwang, Rivo Ronaldo (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The purpose of this research is to explore, describe, and examine the theological essence in the Oratorium liturgy worship. The focus of the research is on the Oratorium liturgy at the Gmibm Pniel Tumobui congregation. Research on the Oratorium liturgy uses qualitative research with data collection techniques, namely observation, interviews, and literature review. The results showed that Oratorium liturgical worship is a form of Christian worship that emphasizes the meeting place between God and the congregation. Existence-essence in Oratory theology as a form of gratitude for the work of salvation bestowed by God for the life of mankind. Therefore, worship using the Oratory liturgy in the congregation of Gmibm Pniel Tumobui is directed to be regular in worshiping God. In addition, the Oratory liturgy is implemented through works of art such as music, chants, and narratives. Through the art of music, singing, and narration, it boosts the emotional-spiritual faith of the congregation of Gmibm Pniel Tumobui, so that they remain faithful in preaching the gospel.